Private Activity in Transport Down for Second Consecutive Year, But Still Around Peak Levels - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Private activity in transport declined in 2008, with the full onset of the financial crisis driving a slowdown in the second half of the year. Yet while investment commitments to transport projects with private participation were down from the peak levels of the previous two years, they remained strong at the third highest level in 1990-2008. In 2008, 56 transport projects with private participation reached financial or contractual closure in 26 low- and middle-income countries. These involve investment commitments (hereafter, investment) of US$23.1 billion. Transport projects implemented in previous years had additional commitments of US$2.9 billion, bringing total investment in 2008 to US$26 billion. That represents a drop of 10 percent from the level reported in 2007. Lower payments to governments (such as concession or lease fees and divestiture revenues) account for the decline. By contrast, investments in physical assets, which amounted to US$22.6 billion in 2008, were up 3 percent from those reported in 2007. The number of projects continued a marked declining trend. The 56 projects reaching closure in 2008 reflected a 40 percent decline from the level in 2007 and a 53 percent drop from that in 2006. The closure of larger projects explains the divergence in trends between investments and number of projects. The average project size grew from US$150 million in 2004 to US$410 million in 2008, while the median rose from US$57 million to US$230 million.